Estilos de vida y su relación con las complicaciones en pacientes con diabetes mellitus tipo 2 de la Asociación de Diabéticos Amigos Dulces del Hospital Isidro Ayora de Loja. - Quezada Costa, Lizzeth del Cisne (2016)
Type 2 Diabetes Mellitus is a public health problem that affects people globally. The lifestyles of these patients themselves play a very important role when evaluating management and treatment programs. This research study was conducted in collaboration with Diabetics Association "Friends Sweets" General Hospital Isidro Ayora City Loja, Ecuador with the aim of linking lifestyles with complications that may occur in patients with Diabetes Mellitus Type 2. The researcher assessed the ages, genders and levels of education and lifestyles using the IMEVID scale, and then relating it to the complications that may arise. Using a descriptive, observational and cross-sectional study, a total of 52 patients who meet the inclusion criteria, and which belong to the aforementioned diabetics, were included in the study. Of the 52 patients, 54% were male and 46% are female; in terms of age, 62% were 65 years old or over; 46% have at least primary education, and, 50% pursue a very healthy lifestyle. As for the relationship of lifestyles with complications, 8% of unhealthy patients had diabetic foot; 4% had retinopathy; 4% nephropathy presented 4% while 2% had neuropathy; 12% of unhealthy patients showed diabetic foot; 8% had neuropathy; 4% had retinopathy; and, 4% had nephropathy. It was concluded that according to the scale of IMEVID, those patients who enjoyed predominantly healthy lifestyles had fewer complications compared with patients who have a unhealthy lifestyles and are more likely to experience complications. Key Words: Type 2 Diabetes Mellitus, Lifestyle